The Nadir Oxygen-Specific Heart Rate Response in Sleep Apnea Links With the Occurrence of Acute Myocardial Infarction - Huang, Zhihua; Wu, Yanpeng; Huang, Kaizhuang; Chen, Pingyan; Chen, Jiyan; Wang, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background Little is known regarding the quantification of sleep apnea- and hypoxemia-elicited heart rate (HR) response and its prognostic significance of the cardiovascular risk. We sought to explore the impact of HR response and variability specific to obstructive sleep apnea (OSA) on the occurrence of a common cardiovascular event – acute myocardial infarction (AMI). Methods Consecutive patients with suspected OSA were enrolled and underwent nocturnal respiratory study and electrocardiography monitoring. The minimal oxygen saturation (minSpO2) was determined from the oxygen saturation curve under a subject-specific search window. Primary HR metrics such as maximal HR in response to minSpO2 and respiratory event-specific HR variability were computed from the synchronized recordings. Multivariate regression analyses were conducted to analyze the associations between individualized HR metrics and the occurrence of AMI. Results Of 2,748 patients recruited, 39% (n = 1,071) had moderate-to-severe OSA (respiratory event index, REI ≥ 15), and 11.4% (n = 313) patients had AMI. Patients with AMI experienced severe OSA, severe minSpO2, and greater HR reactions. Patients with minSpO2 <90% had an adjusted odds ratio (OR) of 1.48 [95% confidence interval (CI): 1.09–2.00, p = 0.012) for AMI. Notably, minSpO2-induced elevated mean HR response (HRmean > 73 bpm) was significantly associated with AMI (OR 1.72, 95% CI: 1.32–2.23, p < 0.001). Patients with both severe minSpO2 (<90%) and elevated HRmean carried an additive OR of 2.65 (95% CI: 1.74–4.05, p < 0.001) for the risk of AMI after adjustment for potential confounders. A large total power spectrum specific to respiratory events was correlated with an adjusted OR of 0.61 for AMI risk. Conclusion Patients with substantial HR reactions to OSA-induced oxygen nadir and restricted cardiac cycle shifting to respiratory events were likely at increased risk of developing AMI. Detection of nocturnal HR response to hypoxemia may help improve cardiovascular risk stratification.